TACIT AND THE SIGNIFICANCE OF YOUR MEMORY - Viveros González, Ana Francisca (Revista de Historia Social y de las Mentalidades, 2011)
Cornelius Tacitus was a prominent roman  historian from the I century AD, has been  extensively studied from various perspectives,  though never studied the trascendence of  the memory in his work, this current analysis  focuses on this. Thus it conceives history  as justice, memory plays a fundamental  role in his story. Therefore, clarify how  Tacitus understood history and his relation  to memory, the relationship between them  and how memory is represented in his  work, trough three categories of analysis,  namely: memory as action, as memories  and as trascendence. This will demonstrate  the integration he made of issues that are  current to our times such as the transmission  of values and the critic judgement made  over the history, but especially the idea that  between history and memory exist a dialectic  that allows the perpetuation of the memory  through the history.
Keywords: Memory; History; Historical Memory